2022
DOI: 10.14740/gr1561
|View full text |Cite
|
Sign up to set email alerts
|

Rates, Reasons, and Independent Predictors of Readmissions in Portal Venous Thrombosis Hospitalizations in the USA

Abstract: Background: Portal vein thrombosis (PVT), generally considered rare, is becoming increasingly recognized with advanced imaging. Limited data exist regarding readmissions in PVT and its burden on the overall healthcare cost. This study aimed to outline the burden of PVT readmissions and identify the modifiable predictors of readmissions. Methods:The National Readmission Database (NRD) was used to identify PVT admissions from 2016 to 2019. Using the patient demographic and hospital-specific variables within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…The NRD is a national database that captures patients' hospitalization, readmissions, and other relevant discharge histories from over 31 different states in the United States. The NRD is a product of the Healthcare Cost and Utilization Project (HCUP), State Inpatient Databases, and the Agency for Healthcare Research and Quality[ 9 ]. The database records over 40 International Classification of Diseases-10 (ICD-10) recognized diagnoses and 25 procedures[ 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NRD is a national database that captures patients' hospitalization, readmissions, and other relevant discharge histories from over 31 different states in the United States. The NRD is a product of the Healthcare Cost and Utilization Project (HCUP), State Inpatient Databases, and the Agency for Healthcare Research and Quality[ 9 ]. The database records over 40 International Classification of Diseases-10 (ICD-10) recognized diagnoses and 25 procedures[ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…The NRD is a product of the Healthcare Cost and Utilization Project (HCUP), State Inpatient Databases, and the Agency for Healthcare Research and Quality[ 9 ]. The database records over 40 International Classification of Diseases-10 (ICD-10) recognized diagnoses and 25 procedures[ 9 ]. It covers approximately 62.2% of the United States population and 60.8% of total hospitalizations in the country[ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to available data, a study has shown that around 0.5% of individuals diagnosed with COVID‐19 have readmission within 30 days due to primary gastrointestinal reasons. The leading factors contributing to these readmissions are gastrointestinal bleeding, intestinal obstruction, acute diverticulitis, acute pancreatitis (AP), and acute cholecystitis 7 . The gut microbiota is crucial in maintaining human health since it is intricately linked to energy metabolism and immunological control.…”
Section: Introductionmentioning
confidence: 99%
“…The leading factors contributing to these readmissions are gastrointestinal bleeding, intestinal obstruction, acute diverticulitis, acute pancreatitis (AP), and acute cholecystitis. 7 The gut microbiota is crucial in maintaining human health since it is intricately linked to energy metabolism and immunological control. The gut microbiota is a critical intermediary for transmitting intestinal illnesses to extraintestinal organs.…”
mentioning
confidence: 99%